Deciphering natural hazard histories based on tree-ring analyses in contrasting tropical ecosystems of Costa Rica - Quesada Román, Adolfo (2020)
UCR::Rectoría::Oficina de Asuntos Internacionales y Cooperación Externa (OAICE)